2019
DOI: 10.4103/ijn.ijn_307_18
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, 1,25-Dihydroxyvitamin D, FGF23, and graft function after renal transplantation

Abstract: Vitamin-D has immuno-modulatory properties besides its role in mineral and bone disorder (MBD) and could have a role in allograft outcome. Fifty-two chronic kidney disease patients on dialysis going for transplantation were prospectively studied before and after renal transplantation. FGF23, 25(OH) vitamin D, 1,25-Dihydroxyvitamin D, PTH, serum Ca, serum PO4, and e-GFR status were evaluated. Vitamin D deficiency was seen in 25.0% of recipients before transplant (26.09 ± 12.19 ng/mL) and in 48.1% at 6 months po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“… 39 One study including 52 kidney transplant recipients found that FGF23 levels were elevated before transplantation but decreased to normal levels within 3 mo posttransplant as eGFR normalized. 40 Another study reported elevated FGF23 levels 3 mo posttransplant, 41 and others have shown persistently elevated FGF23 levels in transplant recipients 1 y posttransplant. 42 Even in kidney transplant recipients with a well-functioning graft >10 y posttransplant, the levels of FGF23 were found to be increased compared with normal controls.…”
Section: Discussionmentioning
confidence: 95%
“… 39 One study including 52 kidney transplant recipients found that FGF23 levels were elevated before transplantation but decreased to normal levels within 3 mo posttransplant as eGFR normalized. 40 Another study reported elevated FGF23 levels 3 mo posttransplant, 41 and others have shown persistently elevated FGF23 levels in transplant recipients 1 y posttransplant. 42 Even in kidney transplant recipients with a well-functioning graft >10 y posttransplant, the levels of FGF23 were found to be increased compared with normal controls.…”
Section: Discussionmentioning
confidence: 95%